2007
DOI: 10.1080/09546630701258093
|View full text |Cite
|
Sign up to set email alerts
|

Anetodermic mastocytosis: Response to PUVA therapy

Abstract: Mastocytosis is a group of disorders characterized by the accumulation of mast cells in different tissues and organs. The skin is the most frequently involved organ (90% of cases) where mastocytosis may show a heterogenic clinical expression. Anetodermic lesions are an unusual clinical presentation of mastocytosis. We report a case of anetodermic mastocytosis in a 26-year-old man, with sparse lesions and a benign course. PUVA therapy obtained excellent results in this case. Darier's sign should be investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…It is reported that mast cells can be directly or indirectly affected by UV radiation (75)(76)(77). Our study contributes to the field by showing that the number of histochemically detectable perifollicular mast cells is decreased while their degranulation is increased 1 day after irradiation of the skin surface with UVA and UVB.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is reported that mast cells can be directly or indirectly affected by UV radiation (75)(76)(77). Our study contributes to the field by showing that the number of histochemically detectable perifollicular mast cells is decreased while their degranulation is increased 1 day after irradiation of the skin surface with UVA and UVB.…”
Section: Discussionsupporting
confidence: 52%
“…Mast cells are important regulators of hair growth and may be functionally important for the maintenance of human HF immune privilege and HF responses to oxidative damage . It has been shown that mast cells are highly affected by UVR , and that UVR or psoralen plus UVA therapy can be beneficial for patients affected by mast cell‐driven skin disorders . Therefore, we were particularly interested in how low or high UVR modulates perifollicular mast cell activities, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Anetodermic lesions are an unusual clinical presentation of mastocytosis. 16,17 MCs play an important role in the development of anetodermic lesions, as they release different mediators which interfere with collagen synthesis and increase the fragmentation of elastic fibers. Moreover, the chemotactic substances released during mastocyte degranulation induce the accumulation of eosinophils, neutrophils and macrophages, which might promote elastase activity.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a literature review using PubMed and Google Scholar search with the keywords “PUVA” and “mastocytosis” for the period from 1970 to 2017. Twenty‐three studies were identified (Table ), most of them reported improvement of pruritus, 2 Darier sign, cutaneous lesions, and/or a decrease in the appearance of new lesions in more than 50% of patients. Nevertheless, only 25% of mastocytosis patients had improvement of skin symptoms for >5 years after cessation of PUVA .…”
Section: Characteristic Features Of Patients With Mastocytosismentioning
confidence: 99%